Eigenvalue Variations of Heisenberg and Quaternion Lie Groups Under the Ricci Flow - Azami, Shahroud; Razavi, Asadollah (Eurasian Mathematical Journal, 2018)
In this article we study the eigenvalue variations of Heisenberg and quaternion Lie groups under the Ricci flow and we investigate the deformation of some characteristics of compact nilmanifolds Γunder the Ricci flow, where N is a simply connected 2-step nilpotent Lie group with a left invariant metric and Γ is a discrete cocompact subgroup of N, in particular Heisenberg and quaternion Lie groups.